Relationships between physical activity, smoking, alcohol use, and health among Finnish male former elite athletes - Kontro, T. (University of Jyväskylä, 2020)
Alcohol- and smoking-related health problems are global issues. Finnish former athletes have lower morbidity than the general population, but little is known about how the continuation of physical activity (PA), smoking, and alcohol use contributes to former athletes` health in later life. The purpose was to investigate how a former elite-level sports career was associated with alcohol use and smoking and health. Furthermore, the aim was to investigate whether all-cause mortality and health habits differ between former athletes and their brothers. Using national registers, the occurrence of alcohol- or smoking-related diseases and deaths among Finnish male former elite athletes (n=2202) and matched controls (n=1403) alive in 1970 was followed from 1970 to 2015. In 1985, 1995, 2001, and 2008, the surviving participants questionnaire-reported their PA, alcohol use, and smoking. The brothers` genealogy and data were collected via a questionnaire sent to them in 2001. Former athletes were more physically active and smoked less than controls in all questionnaires. In 1985, former athletes used alcohol more than controls, especially if their careers had ended by sports injury. Five latent profiles were found. Smoking decreased in all profiles and PA decreased in four profiles. The cross-lagged path model indicated that the associations of alcohol use and PA were weak at most. The risk of alcohol-related morbidity did not differ between former athletes and controls, but the risk of chronic pulmonary diseases or deaths was lower among former athletes. In 2001 health habits were better among former athletes and they survived 2-3 years longer than their brothers. Although the risk of excessive alcohol use increased in individuals whose athletic careers ended by sports injury, overall PA and alcohol use affected each other`s development only modestly during the follow-up. In 1985 former athletes reported higher alcohol use than controls, but there was no difference in alcoholrelated morbidity. The ability to compete at the highest level of sports in young adulthood is associated with a reduced risk of chronic pulmonary disease in later life. Genetic differences between former athletes and brothers, aerobic training for elite endurance sports, and a healthier lifestyle may all contribute to reduced mortality. Keywords: alcohol, chronic disease(s), cohort study, former athlete(s), morbidity, mortality, physical activity, smoking [showless]